The Living Application of Qur’anic Legal Norms in the Indonesian Legal System: A Systematic Review of Ayat al-Aḥkam - Yasir, Muhammad (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2025)
This article systematically examines how Qur’anic legal verses (ayat al-aḥkām) have been implemented in Indonesia’s formal legal system between 2010 and 2024. Using a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 protocol, nine peer-reviewed journal articles were selected from seven academic databases. The findings indicate that the legislative reception of ayat al-aḥkām varies significantly across legal domains. Economic law shows the most structured integration, with verses on zakat, riba, and halal consumption codified through clear statutory instruments and supported by functional institutions. In contrast, criminal law provisions—such as hand-amputation and public lashing—face hermeneutic reinterpretation and procedural constraints, limiting their operational impact. Family law demonstrates interpretive adaptability, where issues like polygamy and inheritance are mediated through maqāṣid-oriented readings and legal safeguards. Rather than static injunctions, these verses exhibit a living character—negotiated, reinterpreted, and embodied within contemporary legal and institutional settings. Across domains, Qur’anic legal norms “live” through contextual engagement with doctrinal consensus, institutional readiness, and political feasibility. These findings reaffirm Indonesia’s dynamic and negotiated approach to Islamic legal integration, suggesting that future Qur’an-based legislation will depend as much on contextual alignment as on textual authority.